Concurrent Bilateral Anterior Tibial Stress Fractures and Vitamin D Deficiency in an Adolescent Female Athlete: Treatment With Early Surgical Intervention - Chung, Jane S.; Sabatino, Meagan J.; Fletcher, Amanda L.; Ellis, Henry Bone (Frontiers in Pediatrics, 2019)
Abstract Case: A 16-year-old African American multi-sport female athlete presents with bilateral worsening activity-related leg pain for five months. Multiple bilateral anterior tibial diaphyseal stress fractures and significant vitamin D deficiency were identified. She was treated with a combination of vitamin D supplements and static intramedullary nailing of the bilateral tibias resulting in clinical and radiographic healing and return to sports. Discussion: Vitamin D deficiency and high level of activity in a young athlete may be the etiology to atypical multiple stress fractures. In athletes who may want to return to sport rapidly, early operative intervention and correction of vitamin D deficiency may be treatment options. Level of Evidence: Level V- case report